SIMULASI MONTE CARLO DENGAN MODEL PERSEDIAAN STOKASTIK PADA PT.BINGEI MEDAN - Roni Jhonson Simamora; Jamaluddin - (STMIK KAPUTAMA, 2018)
Inventory systems or inventory is very important for a company, especially if the company isengaged in the distribution of goods. PT. Bingei Medan is a company engaged in the sale offertilizers. The availability of fertilizers in fulfilling customer orders to be very important, it isnecessary to well-managed inventory. The purpose of this study is to make simulation using theprogramming language Microsoft Visual Basic Version 6.0 and simulations built a simulationmodel of the stochastic inventory system PT. Bingei Medan. And the results of this simulation toanalyze the characteristics of inventory system such as the average level of availability of goods,the amount of goods ordered, the number of items that are not fulfilled (stock out) and the amountof time ordering goods.